Fixation of osteoporotic fractures in the upper limb with a locking compression plate - Neuhaus, V; King, J D; Jupiter, J B (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2012)
Locking Compression Plate (LCP) has the advantageous feature that screws can be locked in the plate leaving an angular stable construct. There is no need to have contact between the plate and the bone to achieve stability resulting from friction of the plate-bone-construct. Therefore the plate does not need to be contoured exactly to the bone and the healing bone's periosteal blood supply is not affected. The LCP is used as a bridging plate to gain relative stability in multi-fragmentary, diaphyseal or metaphyseal fractures. Depending on the fracture, the combination hole can also allow the LCP to achieve absolute stability similar to conventional fixation techniques. Osteoporotic fractures have significant impact on morbidity and mortality. Proximal humeral and distal radius fractures are typical examples. These osteoporotic and often comminuted fractures are ideal settings/indications for LCP utilization in the upper extremity. However, the data quality is due to mostly small study populations not so powerful. Unquestionably there has been a clear and fashionable trend to choose operative treatment for these fractures, because the angular stability allows stable fixation and early functional mobilization.
Keywords: fraktury proximálního humeru; Female; Humeral Fractures; ženské pohlaví; kostní šrouby; fraktury vřetenní kosti; lidé; Osteoporotic Fractures; tříštivé fraktury; Arm Injuries; Bone Plates; Shoulder Fractures; kostní destičky; Male; poranění paže; Fractures, Comminuted; osteoporotické fraktury; mužské pohlaví; fraktury humeru; Radius Fractures; Bone Screws; Humans